Left ventricular non compaction syndrome - timing of delivery. (18th April 2012) - Simpson, P; Pathak, S; McKelvey, A; Freeman, L; Corfe, J; Stanley, K
Abstract : A 37 year old woman with left ventricular non compaction syndrome (an autosomal dominant condition where the left ventricular myocardium remains trabeculated) booked in her first pregnancy at 9 + /40. Preconceptually, she was advised against pregnancy in view of the risks of thrombosis, cardiac failure and arrhythmia. At booking, echocardiography demonstrated an EF (ejection fraction) of 28%, which improved to 36% with Furosemide. Low molecular weight heparin was started as thromboprophylaxis but β blockade was declined by the patient until after 12/40 (Bisoprolol 1.25mg OD). From booking a multi-disciplinary approach was taken. At 28 +2 /40 she developed reduced exercise tolerance and orthopnoea associated with a reduction in her EF to 31%. Her symptoms were managed by titrating up her diuretic doses. At 34 +4 /40 cardiac function deteriorated further (EF = 25%). Delivery was recommended, with steroid cover, but the patient declined this. After discussion with her cardiologist she agreed and a live baby boy was delivered by LSCS under epidural anaesthesia. Post-partum she was cared for on HDU with IV Furosemide and ionotrope support. She was discharged on day five with Furosemide and Amiloride and having converted to Warfarin anticoagulation. Conclusion: The management of cardiomyopathy in pregnancy, particularly when there is poor adherence to medical advice, will be discussed. A proactive and multi-disciplinary approach to her care resulted in a live birth without significant compromise to maternal health.